Computational fluid dynamics (CFD) study of heat radiation from large liquefied petroleum gas (LPG) pool fires. (September 2019) - Yi, Hang; Feng, Yu; Wang, Qingsheng
Abstract: Liquefied petroleum gas (LPG) is flammable and has risks of pool fires during its transportation, storage, and applications. The heat radiation by LPG pool fires poses hazards to individuals nearby and can lead to potential failures of ambient facilities. Due to the high costs and invasive nature of experiments for investigating large-scale pool fires, computational fluid dynamics (CFD) is employed in this study as the cost-effective and noninvasive method to simulate the process and analyze the characteristics of large hydrocarbon pool fires. Specifically, an experimentally validated 3-D CFD model has been built to simulate surface emissive power (SEP) and incident radiation of large-scale LPG pool fires with three different diameters and wind speeds. Steady-state simulations with P1 radiation and probability density function (PDF) combustion models were employed to obtain reliable data after the optimizations based on the comparisons with experimental data and empirical models. The comparison with benchmark experimental data demonstrates that the CFD model employed in this study can accurately predict the incident radiation of large LPG pool fires. A new SEP correlation is also proposed, which is specifically for LPG pool fires with a diameter between 10 m and 20 m. Additionally, the safe separation distances between LPG facilities and surrounded objects have been estimated based on the CFD simulation results. The high-resolution CFD model for large LPG pool fires in this work provides noninvasive and direct quantitative evidence to enhance the fundamental understanding on the safety of large LPG pool fires and can assist regulatory agencies in refining the safety limits in the cost-effective and time-saving manners. Highlights: CFD is employed to simulate the characteristics of large hydrocarbon pool fires. The CFD model can predict surface emissive power and incident radiation of large LPG pool fires. The CFD model has been validated with existing experimental data. Safe separation distances between LPG facilities and surrounded objects have been estimated.